Low surface electromagnetic waves at the metasurface ⁄ dissipative dielectric interface - Galaydych, V.K.; Sporov, A.E.; Olefir, V.P.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2020)
The possibilities of the slow surface electromagnetic waves propagation along the flat boundary of a metasurface with a dissipative dielectric are studied. The metasurface is a thin flat slab of metamaterial with simultaneously negative permittivity and permeability with “amplification”. All media were assumed to be isotropic. Dispersion dependences are obtained for the eigenmodes of such a waveguide structure. The possibility of full compensation of the energy losses of surface waves by the appropriate choice of the “gains” values is demonstrated. Вивчено властивості повільних поверхневих електромагнітних хвиль, що поширюються уздовж плоскої межі метаповерхні з дисипативним діелектриком. Метаповерхня є вузький плоский шар метаматеріалу з негативними як діелектричною, так і магнітною проникливостями з «підсиленням». Усі середовища вважались ізотропними. Отримано дисперсійні залежності власних мод такої хвилеводної структури. Продемонстровано можливість повної компенсації втрат енергії поверхневих хвиль відповідним вибором значень «підсилень». Изучены свойства медленных поверхностных электромагнитных волн, распространяющихся вдоль плоской границы метаповерхности с диссипативным диэлектриком. Метаповерхность представляет собой узкий плоский слой метаматериала с одновременно отрицательными диэлектрической и магнитной проницательностями с «усилением». Все среды считались изотропными. Получены дисперсионные зависимости для собственных мод такой волноводной структуры. Продемонстрирована возможность полной компенсации потерь энергии поверхностных волн соответствующим выбором значений «усилений».